Implementation of Deep Learning in the Planning and Execution of Indonesian Language Instruction in Class XI TKJ at SMK NU 1 Kedungpring - Nia Rahmawati; Anisa Ulfah; Nisaul Barokati Selirowangi (CV. Edujavare Publishing, 2026)
Abstract Deep learning is an approach applied within the *Kurikulum Merdeka* (Independent Curriculum) to foster mindful, meaningful, and joyful learning. This study aims to describe the implementation of deep learning—specifically regarding lesson planning, instructional delivery, and the alignment between the two—in an Indonesian language class for Grade XI Computer and Network Engineering (TKJ) students at SMK NU 1 Kedungpring. A qualitative descriptive approach was employed, with the Grade XI TKJ Indonesian language teacher serving as the subject. Data were gathered through observation, interviews, documentation, and an analysis of teaching modules, then analyzed using the Miles, Huberman, and Saldaña model, involving data condensation, data display, and conclusion drawing. The results indicate that the characteristics of mindful, meaningful, and joyful learning were integrated into lesson planning through the formulation of learning objectives, the use of provocative (inquiry-based) questions, and the design of learning and reflection activities. During instruction, these three characteristics were realized by communicating learning objectives, conducting activities that focused student attention, facilitating discussion and collaboration, connecting material to students' experiences, and creating an active, comfortable learning atmosphere. The alignment between planning and implementation was rated as good, as the majority of activities outlined in the teaching modules were successfully carried out in the classroom. However, certain indicators were not optimally implemented, specifically providing opportunities for all students to offer in-depth responses, integrating the material with the professional context of Computer and Network Engineering (TKJ), and adapting instruction to specific classroom conditions.